The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/bpmj-05-2018-0133
|View full text |Cite
|
Sign up to set email alerts
|

Does supply chain finance improve SMEs performance? The moderating role of trade digitization

Abstract: Purpose A growing need for financing in small and medium enterprises (SMEs) has become a significant obstacle to the development of firms. To remove this barrier, the purpose of this paper is to examine how supply chain finance (SCF) assists the firms to improve their performance by utilizing the resource-based view (RBV). Furthermore, the present study also pursues to test the effect of trade digitization as a moderating variable in the relationship between SC finance and the firm performance. Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 57 publications
(76 reference statements)
3
89
1
1
Order By: Relevance
“…Song et al (2016) used structural equation modelling to establish the relationship between network ties and firm credit concern. (Ali et al, 2018) concluded that SCF adoption factors directly and indirectly improve supply chain effectiveness. (Gao and Xing, 2015) proposed that buyers and suppliers always require credit to run their operations effectively and need risk-free financing solutions to meet their funding requirements, otherwise organizational performance will be affected.…”
Section: Supply Chain Financementioning
confidence: 99%
“…Song et al (2016) used structural equation modelling to establish the relationship between network ties and firm credit concern. (Ali et al, 2018) concluded that SCF adoption factors directly and indirectly improve supply chain effectiveness. (Gao and Xing, 2015) proposed that buyers and suppliers always require credit to run their operations effectively and need risk-free financing solutions to meet their funding requirements, otherwise organizational performance will be affected.…”
Section: Supply Chain Financementioning
confidence: 99%
“…They further stated that SMEs typically face a shortage of financing, hence they are encouraged to invest in innovative projects to respond to challenges. Living in a challenging environment and facing numerous constraints, SMEs use supply chain finance to boost their performance (Ali et al, 2018). Pellegrino and Savona (2017) ascertained how financial constraints cause the failure of innovation in business firms.…”
Section: Entrepreneurial Finance and Enterprise Performancementioning
confidence: 99%
“…The relationship between SCP and firm performance has been extensively discussed in existing literature as it plays a vital role in gaining a competitive advantage and increasing firm productivity (Ali et al , 2018). The concept of supply chain refers to a set of two or more individuals or organizational entities that are directly or indirectly involved in the upstream and downstream flows of goods and services (Mentzer et al , 2001).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%